Theoretical models of ordered alloys of thermoelectric material ternary systems: Chemical bond and state diagrams of In-Cd-Sb - Manyk, O.M.; Manyk, T.O.; Bilynskyi-Slotylo, V.R. (Journal of Thermoelectricity, 2021)
Using the developed comprehensive approach for building theoretical models of ordered alloys of ternary systems of thermoelectric materials, a diagram of the distribution of phase regions for equilibrium in the solid state and isothermal sections based on intermediate binary compounds In-Sb, Cd-Sb, In-Cd are constructed. Calculations of effective charges, effective radii, electron density redistribution, and dissociation energy of nonequivalent hybrid orbitals (NHOs) in the In-Cd-Sb system depending on interatomic distances are presented. The results of theoretical calculations can be used in the development of technology for new thermoelectric materials based on ternary In-Cd-Sb systems. Bibl. 13, Fig. 4, Tabl. 3.